Calcul des coûts unitaires dans les universités francophones - Bottomley, Anthony; Cook, Rupert (Canadian Journal of Higher Education, 1979)
This paper reviews the achievements of a series of studies in cost effectiveness at Francophonie universities conducted under the auspices of the Organization for European Cooperation and Development (OECD) - Centre for Educational Research and Innovation (CERI). It starts by identifying the objectives of these studies and then examines critically the methodology employed, comparing it with work done in Britain, U.S.A. and Canada. Tentative cost comparisons are offered between the French universities studied and one British University. Proposals are made for further research aimed particularly at applying the results in France and elsewhere.